Emergence of Coxsackievirus A16 Causing Childhood Hand, Foot, and Mouth Disease: First Molecular Evidence from Bangladesh - Hoque, Sheikh Ariful; Anwar, Kazi Selim; Khan, Md. Azraf Hossain; Sultana, Ummay Nasrin; Ali, Md. Ahasan; Hossain, Tania; Sharmin, Laila Shamima; Kabir, ARM Luthful; Mollah, Md. Abid Hossain; Hoque, Sk. Azimul; Khan, Masuma; Pham, Ngan Thi Kim; Khamrin, Pattara; Okitsu, Shoko; Hayakawa, Satoshi; Ushijima, Hiroshi (Journal of Pediatric Infectious Diseases, 2023)
Objective Hand, foot, and mouth disease (HFMD), caused by various human enteroviruses (EVs), has emerged in the children of Bangladesh in recent years. However, the etiological agents of HFMD in Bangladeshi children are not yet elucidated. This study aimed to investigate the causative agents with molecular characterization.Methods Viral RNAs were detected from the blister fluid samples by reverse transcription polymerase chain reaction; genotyping was done by sequence-based analysis of the partial viral capsid protein 1 (VP1) region, and the evolutionary relationships among the genotypes were investigated by phylogenetic analysis.Results EV-RNAs were identified in 14 (61%) blister fluid samples out of 23 children who were suspected of HFMD during an outbreak in Rajshahi in 2020. Genome sequence analysis of the VP1 gene was performed on four strains: all the four were coxsackievirus A16 (CVA16) that clustered in B1c subgenotype. These strains showed 95 to 98% nucleotide identity with those reported in India in 2013/2018.Conclusion After our first report on clinical evidence of childhood HFMD in Bangladesh, this time, we provided laboratory confirmation of the emergence of CVA16 as a causative agent of HFMD in Bangladeshi children. There is an urgent need for nationwide, in-depth, clinicoepidemiological surveillance on HFMD including its virology and genetics before it becomes endemic in Bangladesh.
Keywords: HFMD; Bangladesh; CVA16; blister fluid; phylogenetic analysis